Analysis of the Factors Hindering the Improvement of Education Quality at SDN Lambangjaya 02 Tambun Selatan - Ridwan Ridwan; Harri Romadhona; Ifan Sadewa (Green Publisher, 2024)
The success of an educational institution is influenced by the quality of education, as education plays a central role in shaping character and preparing future generations. This research aims to analyze the factors that hinder efforts to improve the quality of education at SD Negeri Lambangjaya 02, Tambun Selatan. This research uses a qualitative approach of case study type. Data collection was conducted using interview, observation, and documentation techniques. The data analysis was carried out through data collection, data reduction, data presentation, and drawing conclusions. The research results indicate that the obstacles to improving the quality of education at State Elementary School Lambangjaya 02 include limited facilities and infrastructure, a lack of parental involvement, and challenges in school management. Thus, this requires the role of various elements such as school management, teacher qualifications, parental support, and educational facilities in improving the quality of education.